Associating liver partition and portal vein ligation for staged hepatectomy (ALPPS): Impact of the inter-stages course on morbi-mortality and implications for management. Issue 5 (May 2015) - Truant, S.; Scatton, O.; Dokmak, S.; Regimbeau, J.-M.; Lucidi, V.; Laurent, A.; Gauzolino, R.; Castro Benitez, C.; Pequignot, A.; Donckier, V.; Lim, C.; Blanleuil, M.-L.; et al.
Abstract Background Associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) was recently developed to induce rapid hypertrophy and reduce post-hepatectomy liver failure in patients with insufficient remnant liver volume (RLV). However, mortality rates >12% have been reported. This study aimed to analyze the perioperative course of ALPPS and to identify factors associated with morbi-mortality. Methods Between April 2011 and September 2013, 62 patients operated in 9 Franco-Belgian hepatobiliary centres underwent ALPPS for colorectal metastases (N = 50) or primary tumors, following chemotherapy (N = 50) and/or portal vein embolization (PVE; N = 9). Results Most patients had right (N = 31) or right extended hepatectomy (N = 25) (median RLV/body weight ratio of 0.54% [0.21–0.77%]). RLV increased by 48.6% [−15.3 to 192%] 7.8 ± 4.5 days after stage1, but the hypertrophy decelerated beyond 7 days. Stage2 was cancelled in 3 patients (4.8%) for insufficient hypertrophy, portal vein thrombosis or death and delayed to ≥9 days in 32 (54.2%). Overall, 25 patients (40.3%) had major complication(s) and 8 (12.9%) died. Fourteen patients (22.6%) had post-stage1 complication of whom 5 (35.7%) died after stage2. Factors associated with major morbi-mortality were obesity, post-stage1 biliary fistula or ascites, and infected and/or bilious peritoneal fluid at stage2. The latter was the only predictor of Clavien ≥3 by multivariate analysis (OR: 4.9; 95% CI: 1.227–19.97; p = 0.025). PVE did not impact the morbi-mortality rates but prevented major cytolysis that was associated with poor outcome. Conclusions The inter-stages course was crucial in determining ALPPS outcome. The factors of high morbi-mortality rates associated with ALPPS are linked to the technique complexity.